Life-cycle study on semi intensive green roofs. (15th June 2017) - Vacek, Petr; Struhala, Karel; Matějka, Libor
Abstract: Properly designed green roofs are environmentally-friendly type of roofing which attracts increasing attention of both general public and professionals. Their use brings many benefits to people and surrounding environment. But with (excessive) use of man-made materials, environmental impacts of green roofs may unnecessarily increase. This paper focuses on Life Cycle Assessment of four semi intensive green roof assemblies, i.e. common assembly, assembly with added extruded polystyrene providing increased thermal resistance and two assemblies with hydrophilic mineral wool. Apart from increasing thermal insulation, this material also partially substitutes plant substrate and fulfils role of a water reservoir. A 20-year cradle-to-grave model of these assemblies life cycle has been created. The main goal of the assessment is evaluation of influence of added man-made materials (e.g. hydrophilic mineral wool) on the assemblies' total environmental impacts. These materials significantly increase the environmental impacts of the first stages of the assemblies' life cycle. On the other hand, use of these materials reduces the environmental impact in following life cycle stages. According to our calculations, the lowest environmental impacts are related to common green roof assembly without any replacement of the substrate. Highest environmental impacts are related to assembly with added extruded polystyrene panels and assembly with 75% of the substrate replaced by the mineral wool. Proper use of the assessed hydrophilic mineral wool increases the environmental impacts by approximately 11%, compared to the common assembly. To sum up, irrespective of other advantages (e.g. water retention potential) we can conclude that this material is suitable for green roofs, almost comparable to natural substrates (from the defined cradle-to-grave perspective).